The socialist blues? Citizenship, class and civil society - Stevenson, Nick (Wiley, 2014)
This article seeks to explore the relationship between the British labour movement, the Left and the Labour party. It does so through the intellectual prism of debates around citizenship and civil society. In this respect, I seek to recover a critical politics around questions of class from the New Left who were always critical of more mainstream ideas of citizenship. However, I also point to the limitations of those who have argued that meaningful forms of citizenship can no longer be connected to political parties and only occurs outside of state organizations. Political parties continue to need intellectual narratives to legitimate their role in society and to connect with the broader civil order.The Labour Party in this respect has seemingly broken with ‘New Labour’ and is searching for a new narrative. The rise of an intellectual grouping around ‘Blue Labour’ has made considerable headway recently and I seek to take a critical view of some of their ideas and ethical frameworks. Here I argue that changing class formations and a more pluralistic society potentially ask difficult questions of those who seek to revive the labour movement in troubled times.